Choosing small sets of policy-relevant scenarios by combining vulnerability and diversity approaches. (October 2016) - Carlsen, Henrik; Lempert, Robert; Wikman-Svahn, Per; Schweizer, Vanessa
Abstract: Computer simulation models can generate large numbers of scenarios, far more than can be effectively utilized in most decision support applications. How can one best select a small number of scenarios to consider? One approach calls for choosing scenarios that illuminate vulnerabilities of proposed policies. Another calls for choosing scenarios that span a diverse range of futures. This paper joins these two approaches for the first time, proposing an optimization-based method for choosing a small number of relevant scenarios that combine both vulnerability and diversity. The paper applies the method to a real case involving climate resilient infrastructure for three African river basins (Volta, Orange and Zambezi). Introducing selection criteria in a stepwise manner helps examine how different criteria influence the choice of scenarios. The results suggest that combining vulnerability- and diversity-based criteria can provide a systematic and transparent method for scenario selection. Highlights: Describes an optimization-based method for choosing a small number of scenarios. A combination of criteria related to vulnerability and diversity is used. The method is applied to a real case involving climate resilient infrastructure.